Correlation of the bottom turn technique with the scores attributed in high performance surfing. DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n5p554 - Juarez Vieira Nascimento; Pedro Caetano Souza; Marcos Augusto Rocha; Juarez Vieira Nascimento; Pedro Caetano Souza; Marcos Augusto Rocha (Universidade Federal de Santa Catarina, 2012)
The surf contests worldwide have presented a high and homogeneous level of performance by the athletes. Thus, the hypothesis that the bottom turn (BT), curve on the base of the wave which is essential to the construction of subsequent maneuvers, might influence the results in high performance competitions. The objective of this study was to quantify the time taken in the execution of the BT by the athletes and correlate it to the scores awarded. The research sample was composed of four contests of the Surfing World Tour. Four heats of each contest were assessed, in a total of sixteen heats studied. The analysis of each BT was performed by using the video split feature available in the Sony Vegas Pro 10.0 software. The statistic analysis was performed with the software SPSS 18.0. The Pearson correlation coefficient was calculated with a significance level of p<0.01. According to the correlations, there was an association between the variables for 87.5% of the cases. Results show that the increase of the curve in the base of the wave (BT) can maximize the performance potential of the surfers, suggesting that BT is a fundamental technical aspect in the construction of subsequent maneuvers that suit the judging criteria of this category.